Polypropylene/myristic acid assisted electrodeposition of eco-friendly micro-engineered copper superhydrophobic coating for enhancing hydrophobicity and anti-corrosion efficiency of an aluminium substrate - Himanshu Prasad Mamgain; Krishna Kanta Samanta; Rajeev Gupta; Ranjeet Brajpuriya; Pravat Ranjan Pati; Jitendra Kumar Pandey; Abhijit Bhowmik; Abdulaziz AlHazaa (Journal of Materials Research and Technology)
Corrosion poses a significant threat to the longevity and integrity of metallic structures, leading to substantial economic losses globally. Traditional corrosion protection methods often have drawbacks, such as increased thickness, altered physical properties, and environmental concerns. In recent years, superhydrophobic coatings have emerged as promising solutions for corrosion protection due to their exceptional water-repellent properties. This research investigates hydrophobicity and corrosion resistance enhancement in eco-friendly copper-coated aluminium through further modification with polypropylene/myristic acid (PP/MA). Electrodeposition of copper on aluminium substrate resulted in a distinctive rose flower-like micro-order rough structure, elevating the contact angle from 58° to 140° (highly hydrophobic) when voltage varying up to 10 V, with the highest hydrophobicity observed at 8 V. Subsequent modification with PP/MA (4:1) further increased the contact angle to 148° (superhydrophobic) and reduced the surface energy, enhancing hydrophobicity. Measurements of corrosion resistance exhibited substantial enhancements, with anti-corrosion efficiency achieving 99%, polarisation resistance at 91200 Ω cm2, and a minimal corrosion rate of 0.000132 mm/year. The enhanced corrosion resistance is due to the rough structure, which reduces electrolyte contact and minimises the surface area exposed to the electrolyte. The stability studies demonstrated that the altered superhydrophobic coating retained a contact angle exceeding 120° even when subjected to severe conditions such as elevated temperatures (up to 180 °C), high pressure, and a 52-day submersion in a 3.5% NaCl solution. The stability of polypropylene is due to the presence of strong metallic and coordination bonds, as well as the inertness and strength of the material itself. These results indicate that the modified coating producing long-lasting hydrophobic and corrosion-resistant characteristics, making it suitable for various industrial applications.